Variasi leksikal Bahasa Melayu Malaysia dan Bahasa Indonesia: suatu analisis dari perspektif kata (Jurnal Bahasa, 2008)
Malay language in Malaysia and Indonesia are of Malay variety. Both of the languages inherit from the same core of language. After achieved independence, the development of the language became more diverged. The purpose of this article is to highlight the divergence compared to convergence in Malay lexical. Kamus Dewan forth edition (KD) and Kamus Besar Bahasa Indonesia, third edition (KBBI) has been selected as the main source of this study. The researcher has idented seven patterns of lexical treatment at the word level. The first pattern shows that the same word in BMM and BI has different semantic components. The second shows that the same word has both different and similar semantic components. The third shows that the same word has similar semantic components. The fourth shows that a word does not have a semantic pair; i.e. a BMM word found in the KD does not have its pair in the KBBI. The fifth pattern shows that a word has similar concepts but have different components (unknown to other variety). The sixth pattern shows a word has similar concepts but different component (accepted in one or both variety). The final pattern shows same word, but different in style and temporal. This article tries to highlight several lexical divergences that may hinder the effectiveness in communication competence among native speakers in Malaysia and Indonesia.